Isolation and Identification of Plant Growth Promoting and Chromium Uptake Enhancing Bacteria from Soil Contaminated by Leather Tanning Industrial Waste - Retno Rosariastuti,; Irfan Dwidya Prijambada,; Ngadiman,; Gani Sisca Prawidyarini ,; Angry Rosha Putri, (Journal of Basic & Applied Sciences, 2013)
Hexavalent chromium is considered as a priority pollutant. Phytoremediation has been widely pursued for the cleanup of heavy metal from contaminated area. The success of phytoremediation is depending on two factors: metal accumulating capability and biomass production of the plants. This paper reports on the isolation and characterization of rhizobacteria having ability to promote plant growth and increase its chromium uptake. Thirty nine of bacterial isolates were obtained from the rhizosphere of wild plants (Sida sp., Sida acuta, Sida rhombifolia, Eupatorium sp., Acelypha sp, Acelypha indica, Amaranthus caudatus, Borreria sp., Leucas lavandulifolia, Eleusine indica, Pennisetum purpurium, Imperata cylindrical, and Vigna sinensis) grow well on soil contaminated by leather tanning industrial waste. Three isolates, namely I26, I30, and I37, have an ability to enhance biomass production of maize (Zea mays) by 2.3, 2.6, and 4.0 times higher compare to the uninoculated one, respectively. The isolates also have an ability to increase chromium uptake by the maize from 7 to 14times. All of the isolates increase the accumulation of Cr in the maize root.The 16S rDNA gene sequence of the isolates relates them to Agrobacterium tumefaciens.